83 Classification of systemic lupus erythematosus patients: the 2018 EULAR/ACR criteria vs the 1982/1997 ACR criteria. A comparative study in two multicenter multiethnic cohorts. (April 2019) - Ugarte-Gil, Manuel F; Pons-Estel, Guillermo J; Griffin, Russell; Harvey, Guillermina B; Wojdyla, Daniel; Vila, Luis M; Massardo, Loreto; Bonfa, Eloisa; Cardiel, Mario; Saurit, Verónica; Soriano, Enrique; Pons-Estel, Bernardo; et al.
Abstract : Background: The 2018 EULAR/ACR criteria for the classification of patients with systemic lupus erythematosus (SLE) has been a work in progress over the last five years. They have been presented and proposed over the last couple of years being their goal to improve the sensitivity and specificity of the previously published SLE criteria. The aim was to determine the sensitivity of the 2018 EULAR/ACR criteria using two well-defined lupus cohorts. Methods: Patients from two well-defined multiethnic and multicenter lupus cohorts, one from the US and the other from Latin America were included. SLE was defined in the US cohort using the 1982/1997 ACR criteria and as diagnosed by the physician for the Latin American cohort although more than 95% of these patients also achieved the 1982/1997 ACR criteria. For these analyses the 1982/1997 ACR criteria were used as the gold standard. Demographics and disease activity at baseline were compared in order to determine differences between those patients who achieved the EULAR/ACR criteria before, at the same time or after than 1982/1997 ACR criteria. Results: Five-hundred and fifty-eight patients out of 640 from the US cohort and 956 out of 1047 from the Latin American cohort achieved the EULAR/ACR criteria. The sensitivity of the EULAR/ACR criteria in the US cohort was 87.2% and in the Latin American cohort was 91.3%; in the US cohort, 41 (7.3%) achieved the EULAR/ACR criteria earlier, 344 (61.6%) at the same time and 173 (31.0%) later than the ACR criteria; for the Latin American cohort these numbers and percentages were 71 (7.4%), 556 (58.2%) and 329 (34.4%), respectively. Patients who achieved the EULAR/ACR criteria earlier were less likely to be Caucasian; disease activity (measured with the SLAM: systemic lupus activity measure for the US cohort, and with the SLEDAI: Systemic Lupus Erythematosus Disease Activity Index for the Latin American cohort) did not differ between the groups. These data are depicted in table 1 . Conclusions: The sensitivity of the 2018 EULAR/ACR criteria against the 1982/1997 ACR criteria (gold standard) was high (87.2% for the USA and 91.3% for the Latin American cohort). While the large majority of patients were classified at the same time (58.2% to 61.6%) with both criteria, about one third were classified later and a small proportion (about 7%) were classified earlier with the 2018 EULAR/ACR criteria. Further examination of the 2018 EULAR/ACR criteria is warranted. Funding Source(s): None